2008
DOI: 10.1007/s00439-008-0488-6
|View full text |Cite
|
Sign up to set email alerts
|

IL1B gene promoter haplotype pairs predict clinical levels of interleukin-1β and C-reactive protein

Abstract: Interleukin-1beta (IL-1beta) activates inflammatory mediator cascades and has been implicated in the pathogenesis of several diseases. Single nucleotide polymorphisms (SNPs) of the IL1B promoter have been associated with various inflammatory diseases. We recently reported that IL1B gene transcription was influenced by four promoter SNPs, and that individual SNP function in vitro was governed by haplotype context. In the present study we tested the in vivo relevance of this observation by comparing IL1B promote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
68
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(72 citation statements)
references
References 48 publications
3
68
0
1
Order By: Relevance
“…27,28 Interleukin 1 is one of the first cytokines implicated in inflammation of the vessel wall during tooth movement, affecting leucocyte recruitment and transmigration. [29][30][31][32][33] Closely connected to this, the function of interleukin 1 is antagonized by the IL1ra protein encoded in the IL1RN gene, wherein specific sequence variants have been associated with an increased predisposition to suffer OIEARR.…”
Section: Discussionmentioning
confidence: 99%
“…27,28 Interleukin 1 is one of the first cytokines implicated in inflammation of the vessel wall during tooth movement, affecting leucocyte recruitment and transmigration. [29][30][31][32][33] Closely connected to this, the function of interleukin 1 is antagonized by the IL1ra protein encoded in the IL1RN gene, wherein specific sequence variants have been associated with an increased predisposition to suffer OIEARR.…”
Section: Discussionmentioning
confidence: 99%
“…5 We found higher frequency of a haplotype containing four SNPs (G-3893A, G-1464C, C-511T and T-31C), where À3893G, À1464G, À511C and À31T were associated with lung cancer risk and higher expression of the IL1B gene in normal lung tissue from lung cancer patients. 5 A few prior studies have investigated the À1464, À511 and À31 SNPs either as a haplotype or single SNPs, [5][6][7][8][9][10][11][12][13] but little is known about the IL1B À3893 SNP. Epidemiological studies show risk association with the IL1B À511 SNP, 7,13 but functional studies show little biological evidence for this polymorphism, and therefore IL1B À1464 and À31 SNPs have received more attention.…”
Section: Introductionmentioning
confidence: 99%
“…The C-511T and T-31C polymorphisms are in near-complete linkage disequilibrium and T-31C is a TATA-box polymorphism that markedly affects DNA-protein interactions in vitro [139,140]. These polymorphisms may affect IL1B expression by changing affinity for transcription factor binding or creating new binding sites for other transcription factors [82,141]. The SNPs may also interact with each other forming various haplotype structures.…”
Section: E Il-1d -/- Il-1e -/- Il-1de -/-(Double Knock Out) or Il1ramentioning
confidence: 99%
“…The SNPs may also interact with each other forming various haplotype structures. Several studies have shown that studying SNPs as haplotypes may better explain the interindividual differences in IL1B expression [82,141].…”
Section: E Il-1d -/- Il-1e -/- Il-1de -/-(Double Knock Out) or Il1ramentioning
confidence: 99%